Colloidal chitin nanogels: A plethora of applications under one shell. (20th January 2016) - Vishnu Priya, M.; Sabitha, M.; Jayakumar, R.
Highlights: Colloidal chitin nanogels are highly versatile nanocarriers. Chitin nanogels can be prepared by simple regeneration technique. Drugs, quantum dots and metallic nanopaticles can be incorporated into nanogels. Chitin nanogels have applications in drug delivery, imaging, sensing and therapy. Abstract: Chitin nanogels (CNGs) are a relatively new class of natural polymeric nanomaterials which have a large potential in the field of drug delivery and nanotherapeutics. These nanogels being very biocompatible are non-toxic when internalized by cells. In this review various properties, preparation techniques and applications of CNGs have been described. CNGs because of their nano-size possess certain unique properties which enable them to be used in a number of biomedical applications. CNGs are prepared by simple regeneration technique without using any cross-linkers. Various polymers, drugs and fluorescent dyes can be blended or incorporated or labelled with the chitin hydrogel network. Drugs and molecules encapsulated within CNGs can be used for targeted delivery, in vivo monitoring or even for therapeutic purposes. Here various applications of CNGs in the field of drug delivery, imaging, sensing and therapeutics have been discussed.